AD, Volume 28, n° 1 & 2, 2003 - Full Issue - Journal System, (Africa Development, 2022)
Contents Introduction Chachage Seithy L. Chachage & Karuti Kanyinga ......................1 The Contradictory Position of 'Tradition' in African Nationalist Discourses: Some Analytical and Political Reflections Michael Neocosmos ............................17 Citizenship and Partitioned People in East Africa: The Case of the Wamaasai Chachage Seithy L. Chachage .....................53 Narrating National Identity: Fiction, Citizenship and the Asian Experience in East Africa Danson Kahyana ....................................97 Globalizing Ethnicity, Localizing Citizenship: Globalization, Identity Politics and Violence in Kenya's Tana River Region Peter Mwangi Kagwanja ..................112 Citizenship and Rights: The Failures of the Post-Colonial State in Africa Karuti Kanyinga & Musambayi Katumanga ...........................153 Ambiguous Transitions: Mediating Citizenship Among Youths in Cameroon Jude Fokwang .............................173 Book Reviews/ Revues de livres Michel Ben Arrous, Coalition, Dispersion, un moment démocratique en Afrique de l'Ouest «francophone», 1988-1998, CODESRIA, 2003 Alawadi Zelao ..............................202 Lydie Moudileno, 2003, Littérature francophones des années 1980 et 1990, CODESRIA, 2003 Blaise Tsoualla ..............................206